FORMATION AND DEVELOPMENT OF EXISTENTIAL THEOLOGY IN A HISTORIOGRAPHICAL PERSPECTIVE - Shevchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines the correlation and mutual influence of Christian theology and existentialism in the context of the formation and development of existential theology. Although existentialism has long been studied in both religious and atheistic forms, its methodological and ideological interaction with Christian theology, especially in post-existentialist thought, remains insufficiently explored. The aim and tasks. The aim of this investigation is to analyze the specifics of the correlation and mutual influence of Christian theology and existentialism. The tasks are to scrupulously cover a wide range of both foreign and Ukrainian sources devoted to the study of the works of representatives of existential theology, primarily Howard Alexander Slaatte and Merold Westphal. Research methods. The research methodology consists of systemic, historical, dialectical and analytical approaches, which allowed us to objectively analyze and interpret the multifaceted processes of integration of existentialism with theology. Due to the use of comparative, hermeneutic and contextualization methods, we managed to compare, contrast and synthesize diverse ideas, views and assessments of researchers of the heritage of outstanding theologians, who are little known in Ukraine. Research results. The study shows that existential theology develops as a specific form of interaction between existentialist philosophy and Christian theological thought. Howard Alexander Slaatte represents this development through eschatological-existential dialectics and the Kierkegaardian-Berdyaevian tradition, while Merold Westphal demonstrates a movement from existential phenomenology toward hermeneutical phenomenology. Discussion. The discussion clarifies the methodological problem of classifying Slaatte and Westphal as existential or post-existentialist thinkers. Their works demonstrate that existentialist, phenomenological, and hermeneutical approaches can be integrated into Christian theological thought. Conclusions. Numerous foreign studies confirm a rather obvious arbitrariness in the definition and classification of the main postulates of religious philosophers and theologians, both existentialists and existential thinkers, which indicates the presence of methodological contradictions in the assessment of the phenomenon of classical existentialism in general and existential theology in particular.